Analisis Efektivitas Saluran Suku Bunga dalam Transmisi Kebijakan Moneter terhadap Sektor Industri Indonesia Pada Periode 2016:09-2025:12 - Clarisa Angelita Heriadi; Irma Febriana MK; Dian Fajarini (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study analyzes the effectiveness of the interest rate channel in transmitting monetary policy to Indonesia's industrial sector. The BI-Rate operates through a complex transmission chain from lending rates (SBK) and credit growth (GKD) to industrial output (GPI). Previous research generally examined these channels separately, leaving the price-to-quantity mechanism not fully integrated. This study aims to analyze the channel's effectiveness and measure the contributions of the BI-Rate, SBK, and GKD in explaining industrial production fluctuations. An explanatory quantitative approach with a Vector Autoregression (VAR) model is employed using monthly secondary data from Bank Indonesia and the Central Statistics Agency, including a COVID-19 dummy as a control variable. Analysis utilized stationarity tests, optimal lag tests, Granger causality, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). IRF results show BI-Rate shocks are positively and significantly responded to by SBK, peaking at 0.062% in the tenth period. GKD response to SBK fluctuated. GKD shocks elicited a same-direction response from GPI, peaking significantly at 1.715% in the fourth period. FEVD analysis revealed credit growth contributed most to industrial growth variance (5.54%), surpassing the BI-Rate (4.84%) and SBK (4.81%). These findings demonstrate that the interest rate channel, through the credit quantity effect, is dominant, warranting reinforcement with macroprudential instruments to encourage productive intermediation.